Influence of Bank Liquidity on Economic Growth of Nigeria - Sayedi, Shuaib Ndagi; Ringim, Kabiru Jinjiri (Lapai Journal of Economics, 2018)
This study investigates the influence of Deposit Money Banks’ (DMBs) liquidity on economic growth of Nigeria measured by Gross Domestic Product (GDP from 1981 to 2014. The population of the study is 64 DMBs that include 45 defunct and 19 existing DMBs operating in the Nigeria banking industry as at December 2015. The regression results indicate that DMBs’ reserves have a positive and significant influence on economic growth. Also, DMBs’ loan to deposit ratios has a negative and significant influence on economic growth. However, DMBs’ liquidity ratios have a negative and insignificant influence on the economic growth of Nigeria. Therefore, this study recommends that the management of DMBs should increase their deposits with CBN as reserves. This is because an increase in the bank’s reserve will increase the economic growth of Nigeria immensely. Also, the management of DMBs should increase the percentage of loan to deposit liabilities ratio. This is because a decrease in the ratio will gradually destroy the economy of Nigeria as fewer funds will be a channel to the productive sector of the economy.